S. Krymsky’s interpretation of sophia-god’s wisdom in philosophy of H. Skovoroda - Матюхіна, О. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
In the article, on the basis of S. Krymsky’s philosophical conception of Sophia-God’s wisdom in philosophy of H. Skovoroda as a climaxof Ukranian philosophy is analized.